P171 Health inequality exists in pirfenidone prescription for idiopathic pulmonary fibrosis in the english midlands according to patient location. (15th November 2016) - Woodhead, FA; Townsend, S; Desai, D
Abstract : Background: Pirfenidone is approved in England by NICE for the treatment of Idiopathic Pulmonary Fibrosis (IPF) but its prescription is limited to certain specialised centres. We hypothesised that this may lead to health inequality in the access to the drug per head of population in an area of the Midlands Methods: 2 prescribing centres (PC), and 4 non-prescribing centres(NPC) referring into them were studied. They were the George Eliot Hospital (GEH) in Nuneaton and South Warwick FT (SWFT) in Warwick (both NPCs) referring to University Hospitals of Coventry & Warwickshire (UHCW) in Coventry, and Kettering General Hospital (KGH) and Northampton General Hospital (NGH), (both NPCs) referring to Glenfield Hospital, University Hospitals of Leicester (UHL). The number of patients prescribed pirfenidone up to January 2016 was collected, and corrected per 100, 000 head of population according to the patient postcode from 2011 census data. All patients were from the CV, LE or NN postcode areas. As data were not normally distributed, analysis was performed with non-parametric statistics using 'R', a statistics package. We collected the time and distance of travel to patients' local hospital, and to their PC. Results: There were a total of 64 postcode areas (PCAs) in the region. Travel times to local hospitals (either a PC or NPC according to area) were normally distibuted with a median of 19 minutes (range 5–40). Travel time to relevant PC was bimodally distributed, with a median of 26 ½ minutes (range 5–64). This was significantly different (p, 1*10^−7). There were no pirfenidone patients in 20 PCAs. Where patients' local hospital was a NPS there were significantly more pirfenidone-free PCAs (15/32) than where the local hospital was a PC (5/32), p = 0.015. Median number of pirfenidone patients per 100, 000 population was significantly less (2.18) where the local hospital was a NPC than where the local hospital was a PC (4.76), p = 0.019. There were also significant differences across all 6 hospitals in the median prevalence of pirfenidone prescriptions (p = 0.003). Conclusions: Our data suggest there are significant health inequality in access to pirfenidone according to patients' location and whether their local hospital is a PC or not.